2006
DOI: 10.1038/nature04974
|View full text |Cite
|
Sign up to set email alerts
|

DNA overwinds when stretched

Abstract: DNA is often modelled as an isotropic rod, but its chiral structure suggests the possible importance of anisotropic mechanical properties, including coupling between twisting and stretching degrees of freedom. Simple physical intuition predicts that DNA should unwind under tension, as it is pulled towards a denatured structure. We used rotor bead tracking to directly measure twist-stretch coupling in single DNA molecules. Here we show that for small distortions, contrary to intuition, DNA overwinds under tensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

47
443
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(500 citation statements)
references
References 27 publications
47
443
6
Order By: Relevance
“…It is worth noting that in the region near the initial B-DNA structure ( Ͼ 9.5 Å), for which DNA is still in the entropic regime (F Յ 10 pN), we were also able to calculate (see supporting information for details) a twist͞stretch coupling constant of Ϫ15 nm. This finding agrees, both in sign and absolute value, with recent single molecule experiments indicating that, near the B form of DNA, an increase in twist leads to an increase in extension (33,34).…”
Section: Equilibrium Calculations Free Energy and Equilibrium Forces supporting
confidence: 80%
See 2 more Smart Citations
“…It is worth noting that in the region near the initial B-DNA structure ( Ͼ 9.5 Å), for which DNA is still in the entropic regime (F Յ 10 pN), we were also able to calculate (see supporting information for details) a twist͞stretch coupling constant of Ϫ15 nm. This finding agrees, both in sign and absolute value, with recent single molecule experiments indicating that, near the B form of DNA, an increase in twist leads to an increase in extension (33,34).…”
Section: Equilibrium Calculations Free Energy and Equilibrium Forces supporting
confidence: 80%
“…The calculation of the free energy profile in the vicinity of B-DNA has additionally provided an equilibrium twist-elongation dependence (see supporting information) that enabled the calculation, in the low-twist limit, of a negative twist-stretch coupling constant of Ϫ15 nm, in accord with recent experiments (33,34).…”
Section: Concluding Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…From well-defined oligomers of DNA, the stretch-torsion coupling can be obtained via magnetic tweezers and measuring the consequent over-or under-winding of the helix by tracking an attached rotor bead. In the work of Gore et al [7], a stretching elastic modulus is reported, which equates to an inter base-pair force constant of 3 N=m. Another example of a molecular sculpturing approach involves DNA oligomers capped with gold nanoparticles, which allow the end-to-end distance to be measured by small angle x-ray scattering [8].…”
mentioning
confidence: 99%
“…Equation (10) does not predict the tiny anomalous overwinding under tension [15]. We believe this is a consequence of neglecting the bending modes, whose thermal fluctuation weakens the base's bonds.…”
mentioning
confidence: 98%